2018
DOI: 10.1016/j.bbrc.2018.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Citrullinated histone 3 causes endothelial barrier dysfunction

Abstract: Circulating components of neutrophil extracellular traps (NETs), especially histones, are associated with tissue injury during inflammatory conditions like sepsis. Commonly used as a NET biomarker, citrullinated histone 3 (H3Cit) may also functionally contribute to the NET-associated inflammatory response. To this end, we sought to examine the role of H3Cit in mediating microvascular endothelial barrier dysfunction. Here we show that H3Cit can directly contribute to inflammatory injury by disrupting the microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 30 publications
3
64
1
Order By: Relevance
“…In this study, the CitH3 peptide was shown to increase permeability of HUVECs in vitro (Figure 1A). In addition, infusion of CitH3 protein has been shown to induce an extravasation of fluorescent-labeled albumin across mouse mesenteric micro vessels without cell death (25). These observations suggest that CitH3 might be one of the causes for vascular leakage and organ edema in sepsis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this study, the CitH3 peptide was shown to increase permeability of HUVECs in vitro (Figure 1A). In addition, infusion of CitH3 protein has been shown to induce an extravasation of fluorescent-labeled albumin across mouse mesenteric micro vessels without cell death (25). These observations suggest that CitH3 might be one of the causes for vascular leakage and organ edema in sepsis.…”
Section: Discussionmentioning
confidence: 89%
“…The function of CitH3 remains largely unknown. It was recently reported that human recombinant CitH3 protein could disrupt endothelial barrier in vivo, probably through opening cell-cell adheres junctions and reorganizing the actin cytoskeleton (25). This conclusion needs further evaluation since the recombinant CitH3 protein was catalyzed by PAD4 purified from E. coli, and endotoxin contamination can compromise the validity of the experimental results (26,27).…”
Section: Cith3 Increases Huvec Permeability and Induces Net Formationmentioning
confidence: 99%
“…While there are some similarities in the proteins targeted for citrullination by PAD2 and PAD4, some proteins are selectively targeted, and this could account for the differences in the properties of the NETs. A recent report indicates that Cit-H3 promotes dysfunction of the endothelial barrier through reorganization of the actin cytoskeleton (48), and this may explain why mice lacking Padi4 generate NETs devoid of vasculopathic effects. Future studies in mice that genetically lack both PAD2 and PAD4, as well as in vivo use of PAD2-and PAD4-specific inhibitors, will be required to assess whether dual blockade of these pathways promotes synergistic effects in the modulation of autoimmunity and endothelial dysfunction when compared with inhibition of single isozymes, given the effectiveness previously observed with pan-PAD inhibitors in other lupus mouse models (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils were isolated from untreated FVB, Padi2 -/-, or Padi4 -/mice and stimulated with imiquimod (R837; 100 μg/ml; InvivoGen) in serum-free RPMI 1640 for 6 hours at 37°C. NETs were isolated as previously described (47) using 10 U/ml of micrococcal nuclease (Thermo Fisher Scientific) for 15 minutes at 37°C (48). NETs were centrifuged to remove cellular debris and the supernatants stored at -80°C until used.…”
Section: Methodsmentioning
confidence: 99%
“…24 Cultured epithelial cells were incubated with (a) NETs recovered upon stimulation of 1 × 10 6 neutrophils (250 ng/mL); (b) with supernatants of neutrophils incubated with NET inhibitor, DPI (10 µL); (c) with human recombinant citrullinated histone 3, a key component to determine the presence of NETs, (H3Cit, 1 µmol/L), (Cayman Chemical); and (d) with supernatants of unstimulated neutrophils (10 µL) for 24 hours, as described previously. 23,25 Thereafter, cultured cells and supernatant were collected to evaluate the expression levels of chemokines with real-time PCR and ELISA. Epithelial permeability and transepithelial electrical resistance were also measured as described previously.…”
Section: The Effect Of Nets On Chemokine Secretion By Sinus Epithelmentioning
confidence: 99%